Proteome and phosphoproteome analysis of 2,4-epibrassinolide-mediated cold stress response in cucumber seedlings - Zhou, Mengdi; Li, Yansu; Yan, Yan; Gao, Lihong; He, Chaoxing; Wang, Jun; Yuan, Quan; Miao, Li; Li, Shuzhen; Di, Qinghua; Yu, Xianchang; Sun, Mintao (Frontiers in Plant Science, 2023)
The 2, 4-epibrassinolide (EBR) significantly increased plants cold tolerance. However, mechanisms of EBR in regulating cold tolerance in phosphoproteome and proteome levels have not been reported. In this study, phosphoproteome analysis showed that cucumber responded to cold stress through multi-site serine phosphorylation, while EBR further upregulated single-site phosphorylation for most of cold-responsive phosphoproteins. Association analysis of the proteome and phosphoproteome revealed that EBR reprogrammed proteins in response to cold stress by negatively regulating protein phosphorylation and protein content, and phosphorylation negatively regulated protein content in cucumber. Further functional enrichment analysis of proteome and phosphoproteome showed that cucumber mainly upregulated phosphoproteins related to spliceosome, nucleotide binding and photosynthetic pathways in response to cold stress. However, different from the EBR regulation in omics level, hypergeometric analysis showed that EBR further upregulated 16 cold-up-responsive phosphoproteins participated photosynthetic and nucleotide binding pathways in response to cold stress, suggested their important function in cold tolerance. Analysis of cold-responsive transcription factors (TFs) by correlation between proteome and phosphoproteome showed that cucumber regulated eight class TFs may through protein phosphorylation under cold stress. Further combined with cold-related transcriptome found that cucumber phosphorylated eight class TFs, and mainly through targeting major hormone signal genes by bZIP TFs in response to cold stress, while EBR further increased these bZIP TFs (CsABI5.2 and CsABI5.5) phosphorylation level. In conclusion, the EBR mediated schematic of molecule response mechanisms in cucumber under cold stress was proposed.